Expanding Research Horizons: Exploring Less Frequently Used Research Methodologies in Applied Linguistics - DE VEGA, Nofvia; ARIFIN, Arifin; RAHMAN, Andi Dhiyaul; ABIYYU, Raihan Langgeng (Politeknik Negeri Ujung Pandang, 2025)
The book Less Frequently Used Research Methodologies in Applied Linguistics, edited by A. Mehdi Riazi, explores underutilized research methodologies that offer fresh perspectives in applied linguistics. The book presents a range of approaches, including the multiperspectival approach (MPA), multimodal analysis, conversation analysis, grounded theory, phenomenology, narrative inquiry, and the repertory grid technique. Each chapter provides both theoretical foundations and practical applications, such as MPA’s use in art and design communication, multimodal analysis in embodied teaching and textbooks, and conversation analysis in studying avoidance strategies. Grounded theory is examined in the context of extensive reading, while phenomenology sheds light on EFL learners’ experiences of maintaining foreign language proficiency. Narrative inquiry is demonstrated through case studies from Senegal, and the repertory grid technique is explored for its potential in linguistic research. The volume concludes with a critical discussion of the challenges and contributions of these lesser-used methodologies, advocating for their broader adoption. By showcasing these alternative approaches, the book serves as a valuable resource for researchers seeking to expand their methodological repertoire in applied linguistics.